2020
DOI: 10.1186/s13046-020-01637-4
|View full text |Cite
|
Sign up to set email alerts
|

CPEB3 inhibits epithelial-mesenchymal transition by disrupting the crosstalk between colorectal cancer cells and tumor-associated macrophages via IL-6R/STAT3 signaling

Abstract: Background: Crosstalk between cancer cells and tumor-associated macrophages (TAMs) mediates tumor progression in colorectal cancer (CRC). Cytoplasmic polyadenylation element binding protein 3 (CPEB3) has been shown to exhibit tumor-suppressive role in CRC. Methods: The expression of CPEB3, CD68, CD86 and CD163 was determined in CRC tissues. SW480 or HCT116 cells overexpressing CPEB3 and LoVo or RKO cells with CPEB3 knockdown were constructed. Stably transfected CRC cells were co-cultured with THP-1 macrophages… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 45 publications
(50 reference statements)
2
49
0
Order By: Relevance
“…CCL2 production has been reported to be more inducible in HER2+/ER− breast carcinoma cells compared with HER2+/ER+ cells under EGF/HRG stimulation, and enhanced NF-kB transcription levels were detected in HER2+/ER− breast carcinoma cells (5). Emerging evidence indicates that the JAK/STAT pathway can also promote CCL2 production under stimulation (6)(7)(8)(9)(10)(11)(12)(13). Neddylation is a reversible protein modification process mediated by NEDD8.…”
Section: Regulation Of Ccl2 Productionmentioning
confidence: 99%
“…CCL2 production has been reported to be more inducible in HER2+/ER− breast carcinoma cells compared with HER2+/ER+ cells under EGF/HRG stimulation, and enhanced NF-kB transcription levels were detected in HER2+/ER− breast carcinoma cells (5). Emerging evidence indicates that the JAK/STAT pathway can also promote CCL2 production under stimulation (6)(7)(8)(9)(10)(11)(12)(13). Neddylation is a reversible protein modification process mediated by NEDD8.…”
Section: Regulation Of Ccl2 Productionmentioning
confidence: 99%
“…This mechanism was demonstrated since tumorinfiltrating CD11b + CD11c + show profound expression of IL-6 and decreased ability of T-cell stimulation [79]. Cytoplasmic polyadenylation element-binding protein 3 (CPEB3) ex-hibits a tumor-suppressive role in CRC, and has been shown to inhibit EMT by interrupting the crosstalk between CRC cells and tumor-associated macrophages, in an IL-6/STAT3dependent manner [80]. In addition, Th17 cells suppress CD8+ cell migration, which is a prerequisite for the efficacy of immunotherapy, by downregulating CXCR3 expression, through an IL-17A/STAT3 mechanism, in advanced-stage CRC patients [81].…”
Section: Stat3 In Combination With Immunotherapymentioning
confidence: 99%
“…CPEB3, a member of the CPEB family, was discovered to monitor cell translation by adjusting cytoplasmic polyadenylation. It has also been reported that CPEB3 was aberrantly expressed in several types of cancer ( 23 , 30 , 49 ). In a study of ovarian cancer cells, miR-301b-3p increased cell invasion and migration by targeting CPEB3 ( 50 ).…”
Section: Discussionmentioning
confidence: 88%